Circular Economy Sustainability in Developing Countries: A Bibliometric Analysis of Global Trends, Key Themes, and Research Gaps (2017-2025) - Safira Nashirothul Nur Ummah; Retno Mustika Dewi; Riza Yonisa Kurniawan (International Journal of Economics, Science, and Education, 2026)
ABSTRACT Purpose: The main focus of this study is to understand research trends, identify key academic actors, and explore the impact of the circular economy in various dimensions of development. In this way, it is hoped that this study will not only contribute to the development of knowledge but also serve as a reference for policymakers, practitioners, and researchers in developing strategies for the transition to a circular economy in developing countries. Design/methodology/approach: This This study uses a bibliometric approach to identify and map publication trends in circular economy research in developing countries. With this approach, researchers can identify the extent to which the circular economy has become a focus of research, as well as the topics that dominate scientific debate. The bibliographic data collection process involved several stages. The first stage involved entering the terms “circular AND economic AND in AND developing AND country” in the article title field of the Scopus database for the period 2017-2025 with the document type “Article,” which yielded 364 documents. Then, the language was limited to English, resulting in a dataset of 358 articles. To ensure the relevance and accuracy of these articles, a recheck was performed using Microsoft Excel to review the titles, followed by a review of the abstracts for content suitability, with a final result of 168 articles that met all the specified criteria. Findings: The review indicates that growing global attention to the topic. The dominant themes focus on waste management, recycling, and sustainable development, while research trends are gradually shifting toward more empirical, policy-oriented, and interdisciplinary studies. However, gaps remain in integrating renewable energy, social aspects, and circular business models, and scholarly contributions are still concentrated in a limited number of countries, highlighting the need for broader participation and more collaborative, policy-driven research in developing economies Research limitations/implications: This study is limited to the selected database and publication period, which may limit the generalization of the findings. Future research should expand the data sources, apply empirical approaches, and integrate less explored aspects such as renewable energy, social dimensions, and circular business models to strengthen circular economy studies in developing countries. Practical implications: These findings provide insights for policymakers, researchers, and practitioners in identifying key trends and research gaps in circular economy studies. These results can support the development of more effective policies, encourage interdisciplinary collaboration, and guide the implementation of circular economy practices to promote sustainable development in developing countries. Originality/value: This study contributes to the literature by presenting a structured thematic mapping of circular economy research and by identifying emerging themes and potential gaps for future research. Paper type: Literature review